2001
DOI: 10.1161/hh1501.094266
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine, Bradykinin, Opioids, and Phenylephrine, but not Adenosine, Trigger Preconditioning by Generating Free Radicals and Opening Mitochondrial K ATP Channels

Abstract: Abstract-It has been assumed that all G i -coupled receptors trigger the protective action of preconditioning by means of an identical intracellular signaling pathway. To test this assumption, rabbit hearts were isolated and perfused with Krebs buffer. All hearts were subjected to a 30-minute coronary artery occlusion followed by 120 minutes of reperfusion. Risk area was measured with fluorescent particles and infarct size with triphenyltetrazolium chloride staining. Control hearts showed 29.1Ϯ2.8% infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
2
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(210 citation statements)
references
References 43 publications
6
196
2
6
Order By: Relevance
“…These data indicate that specific antioxidant enzymes (SOD or CAT) can or cannot abrogate PostC-triggering. However, large spectrum antioxidants (NAC or MPG) abolish both preconditioning and PostC protection in several settings [8][9][10]13,22,38,51,54,63]. Although the infused enzymes do not easily enter into the cells, enough SOD enters, at least into endothelial cells, to perturb the redox-environment created by PostC (i.e., SOD down-regulation), thus blocking protection.…”
Section: Early Reperfusionmentioning
confidence: 99%
See 3 more Smart Citations
“…These data indicate that specific antioxidant enzymes (SOD or CAT) can or cannot abrogate PostC-triggering. However, large spectrum antioxidants (NAC or MPG) abolish both preconditioning and PostC protection in several settings [8][9][10]13,22,38,51,54,63]. Although the infused enzymes do not easily enter into the cells, enough SOD enters, at least into endothelial cells, to perturb the redox-environment created by PostC (i.e., SOD down-regulation), thus blocking protection.…”
Section: Early Reperfusionmentioning
confidence: 99%
“…Therefore a vicious cycle is likely to be established in the so-called ROS-induced ROS release (RIRR) [26,27,34]; thus inducing ROS stress and reperfusion injury [for reviews see 46,50]. Survival mechanisms in the heart can be triggered by short, non-lethal periods of ischemia and reperfusion, applied either before (preconditioning) or immediately after (postconditioning, PostC) the index ischemia [3,10,20,25,33,[44][45][46]62]. Both in vivo and in vitro ischemic-and pharmacologicalpreconditioning triggering require protective ROS signaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Forbes et al (10) recently demonstrated that diazoxide, a selective mitochondrial K ATP channel opener, generates oxygen radicals and protects ischemic rat hearts. Acetylcholine, bradykinin, phenylephrine, and opioids generate oxygen radicals that were blocked by selective mitochondrial K ATP channel antagonist 5-HD (6,25,38). These data indicate that the mitochondrial K ATP channel is upstream of oxygen radicals in mediating cardioprotection of these agents.…”
Section: Discussionmentioning
confidence: 79%